Physics of nanostructures : (Scottish Universities summer school in physics, 1992)
The revolution in semiconductor physics over the last few years has led to the miniaturization of devices. The aim of the 38th Scottish Universities Summer School was to study the fabrication of these devices, their electron transport and optical properties, and to examine future developments in the field of nanostructures. The early chapters focus on fabrication processes including the use of molecular beam epitaxy and high-resolution lithography. Various theoretical approaches to the electronic properties of nanostructures and complementary experiments are described. The final papers cover a range of optical properties of arrays of nanostructures and discuss the practical applications of optical effects in quantum wires and dots.